The talitrid amphipods of Tonga (Crustacea, Amphipoda, Talitridae) - Lowry, J. K.; Bopiah, Arundathi (Zootaxa, 2013)
One new genus and four species of talitrid amphipods are described from Tonga: Platorchestia ano sp. nov.; Talorchestia spinipalma (Dana, 1852); Tongorchestia pangaimotu gen. nov., sp. nov.; T. towneri sp. nov.